Pengaruh Gender, Budaya, Dan Faktor Lingkungan Terhadap Ethical Beliefs: - Dio Septiawan; Herlina Helmy; Salma Taqwa (Universitas Negeri Padang, 2019)
The purpose of this study was to investigate the influence of gender, culture, the campus environment, and the home environment against ethical beliefs. This study focused on students majoring in accounting in the city of Padang has taken the course of the audit and has not yet taken including the course of the audit. Data collection methods are purposive sampling. Types of data used in this research is the data subject in which type of research data in the form of accounting students in four universities in the city of Padang, Padang State University, Andalas University, Bung Hatta University, and Putra Indonesia University. The data source in the research is primary data. In this research show that there are not prove that women tend to be more ethical in an Ethical audit accounting student ethical beliefs., meanwhile the result of the study show that there are positive influences between culture, Campus environment, and Home environment against the Ethical beliefs has taken courses on auditing and has taken including the course of the audit in students accounting in the city of Padang.